The Social Relations of Productivity: A Longitudinal and Comparative Study of Aluminium Smelters - Edwards, Paul; Bélanger, Jacques; Wright, Martyn (Relations industrielles / Industrial Relations, 2002)
SummaryThis article uses time-series data from two aluminium plants from Canada and the U.K. to analyze the social relations of productivity. The eventual turn to teamwork reflected, not hard evidence that productivity change had dried up, but a belief that they were the next step towards further improvement. By considering the structure of social relations over time in each smelter, we contribute to ongoing debates on the complex connections between productivity growth and organizational innovation. On the basis of direct observation and interviews, the article also reveals some of the social dynamics generating productivity growth and describes the development of idiosyncratic competencies. It stresses how the development of teamwork was historically in line with the productive ethos that had developed over time under continuous process technology.